ANALISIS PERBANDINGAN KINERJA KEUANGAN DENGAN MENGGUNAKAN METODE DUPONT SYSTEM PADA PT. PRIMARINDO ASIA INFRASTUCTURE, TBK DAN PT. SEPATU BATA, TBK - Nanang Yuliana; Aris Munandar; M Rimawan (Jurnal Bina Bangsa Ekonomika, 2023)
This research aims to analyze and determine the difference in the company's financial performance using the Du Pont System method. This type of research is a comparative research with the research instrument in this study is a table list in the form of data on total assets, sales, net profit and equity. The population in this study is the entire financial statements of PT. Primarindo Asia Infrastructure, Tbk and PT. Sepatu Bata, Tbk. The sample used in this study is the financial statements of PT. Primarindo Asia Infrastructure, Tbk and PT. Sepatu Bata, Tbk during the period 2014 – 2021. The sampling technique used is purposive sampling. This research was conducted at PT. Primarindo Asia Infrastructure, Tbk. and PT. Sepatu Bata, Tbk. with data access through www. Idx.com.id. The data were analyzed using Du Pont System analysis independent sample t-test. The results of the study showed that there was no difference in financial performance between PT. Primarindo Asia Infrastructure, Tbk. with PT. Sepatu Bata, Tbk is measured using Du Pont's Return On Investment and Du Pont's Return On Equity approach